2018
DOI: 10.1038/s41386-018-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Deficient inhibition in alcohol-dependence: let’s consider the role of the motor system!

Abstract: Impaired inhibitory control contributes to the development, maintenance, and relapse of alcohol-dependence, but the neural correlates of this deficit are still unclear. Because inhibitory control has been labeled as an executive function, most studies have focused on prefrontal areas, overlooking the contribution of more "primary" structures, such as the motor system. Yet, appropriate neural inhibition of the motor output pathway has emerged as a central aspect of healthy behavior. Here, we tested the hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 43 publications
7
52
1
Order By: Relevance
“…The current findings in GDPs contrast considerably with our prior observations in alcohol-dependent patients (ADPs), which revealed a major lack of preparatory suppression, especially in the patients who relapsed during the year following the testing (9). As GDPs are preserved from the neurotoxic influence of drugs of abuse, one straightforward interpretation of the discrepancy between both studies is that the lack of preparatory suppression observed in ADPs arises as a consequence of chronic alcohol consumption.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current findings in GDPs contrast considerably with our prior observations in alcohol-dependent patients (ADPs), which revealed a major lack of preparatory suppression, especially in the patients who relapsed during the year following the testing (9). As GDPs are preserved from the neurotoxic influence of drugs of abuse, one straightforward interpretation of the discrepancy between both studies is that the lack of preparatory suppression observed in ADPs arises as a consequence of chronic alcohol consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the different processes assisting inhibitory control, an increasing focus has been drawn on mechanisms allowing to downregulate the excitability of the motor system ( 5 ). Accordingly, a drastic suppression of motor activity has been reported when subjects are in the process of stopping an action ( 6 , 7 ), but also during the preparation of motor acts ( 8 , 9 ). In particular, by measuring motor-evoked potentials (MEPs) elicited by single-pulse transcranial magnetic stimulation (TMS) over the primary motor cortex (M1), studies have monitored changes in the excitability of the corticospinal pathway during instructed-delay choice reaction time (RT) tasks ( 10 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also provided us with a very precise measure of the RTs (precision = 1 ms), while controlling for the initial position of the index fingers. This set-up has been used in previously published work (Quoilin et al, 2016, 2018, 2019; Grandjean et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol-dependents exhibit reduced RMT, AMT, and MEPs compared to healthy controls [ 30 , 32 ]. In contrast, other studies report no chronic-related effects on RMT, AMT or MEPs [ 23 , 28 , 31 ].…”
Section: Alcoholmentioning
confidence: 99%